2022
DOI: 10.1177/03009858221128915
|View full text |Cite
|
Sign up to set email alerts
|

Histologic lesions of cestodiasis in octopuses

Abstract: Parasitism of cephalopods is common, including infection with Aggregata spp., Ichthyobodo spp., dicyemids, cestodes of the orders Tetraphyllidea and Trypanorhynchidea, and various crustaceans. Cestodiasis in octopuses is reported, although a full histologic description of lesions has not been previously described. Cestodiasis was identified in 10 octopuses of 4 different species, which included 4 common octopuses ( Octopus vulgaris), 3 Caribbean reef octopuses ( Octopus briareus), 2 two-spot octopuses ( Octopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Comparatively, histomorphologically similar Rickettsia or Chlamydia-like organisms in mollusks have been identified as gammaproteobacterial-Endozoicomonadaceae. 10,27,39 Such organisms are not necessarily correlated with disease; 21,23 however, heavy infections may contribute to pathology, 21,27 and a generalized tissue distribution was identified in a single coconut octopus in this study.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Comparatively, histomorphologically similar Rickettsia or Chlamydia-like organisms in mollusks have been identified as gammaproteobacterial-Endozoicomonadaceae. 10,27,39 Such organisms are not necessarily correlated with disease; 21,23 however, heavy infections may contribute to pathology, 21,27 and a generalized tissue distribution was identified in a single coconut octopus in this study.…”
Section: Discussionmentioning
confidence: 62%
“…This reinforces the hypothesis that such infections should generally be considered incidental, although a recent publication has drawn attention to associated inflammation and necrosis in some cases of cestodiasis in octopuses. 23 Ocular cataracts were seen in 2 cuttlefish and a single common octopus, which could have impaired vision and potentially affected feeding. A recent study of cephalopod ocular pathology identified inflammatory lesions, particularly anterior uveitis, as a frequent presentation, with cataracts in a substantial proportion (36%) of the 33 diagnostic specimens included from mixed cephalopods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its articles were selected to familiarize the readership with emerging issues and pertinent questions, including how to perform mortality investigations in invertebrates. 14,21 It includes several case studies, 1,2,3,9,11,13,17 which demonstrate how traditional investigative and descriptive pathology methods can effectively improve our understanding of invertebrate diseases, even in the face of the many challenges posed by invertebrates. Articles, including studies on arachnids and giant African millipedes, 7,20 bring together current knowledge so as to enable diagnosticians wishing to engage in important frontiers.…”
mentioning
confidence: 99%